Mapping Tropical Dry Forest Gradients in an Andean Region with High Environmental Variability - J. Camilo Fagua; Patrick Jantz (Ecological Indicators)
Tropical Dry Forest (TDF) is one of the most threatened terrestrial environments in the neotropics because of high rates of conversion to agriculture. Despite this high degree of threat, many regions lack detailed maps on the actual extent and boundaries of their TDFs, which is fundamental information for their conservation. We developed a methodological framework to map TDF at 10 m in regions where they grade into other forest types. The approach uses climate variables, altitude, soil properties, and remote sensing data (multispectral and SAR − Synthetic Aperture Radar-SAR imagery) to predict TDF in the Department of Caldas, Colombia. Accuracy of the resulting map was confirmed with field observations (Overall Accuracy = 0.88, Kappa = 0.73, Area Under the Receiver Operating Characteristics Curve = 0.87, and True Skill Statistic = 0.73). We estimated ∼ 54 km2 of TDF, which represents 9.2 % of its potential area of occurrence in the study area. TDF gradually transitions to Tropical Moist Forest (TMF) from two main low altitude river valleys to higher altitudes in the Andes Mountains. With modification, our methods could be applied for mapping TDF in other tropical regions.